Safety and Effectiveness of Transthoracic Core Needle Biopsy in a Newly Established Interventional Radiology Program in Tanzania - Erick M. Mbuguje; Jared M. Alswang; Ivan Rukundo; Azza Naif; Fabian M. Laage Gaupp; Vijay Ramalingam; Murray Asch (The Arab Journal of Interventional Radiology)
Background Transthoracic core needle biopsy (TTCNB) became a routinely offered procedure in Tanzania in October 2018. This study evaluates the safety and effectiveness of establishing a TTCNB program in a resource-limited setting. Methodology A single center, prospective, observational cohort study was conducted at Muhimbili National Hospital on 90 patients who underwent computed tomography-guided TTCNB from October 2018 to May 2021. Patient and procedural data, including demographic information, complications, pathology results, and clinical outcomes, were stored in a Research Electronic Data Capture (REDCap) database. Follow-up was conducted at 4 weeks postprocedure by phone. Descriptive analysis was performed using Statistical Package for Social Sciences. Results A total of 90 patients underwent TTCNB. Seven samples were lost or never processed. In total, 68/83 (81.9%) of processed samples were diagnostic, with 89.7% (n = 61) classified as malignant and 10.3% (n = 7) classified as benign. Overall, 82.4% (n = 56) were classified as primary malignancies, 7.4% (n = 5) as metastatic malignancies, 5.9% (n = 4) as benign tumors, and 4.4% (n = 3) as infectious. Reasons for nondiagnostic samples were crashed/insufficient samples in 53.3% (n = 8) and nonspecific chronic inflammation in 46.7% (n = 7). Minor (Society of Interventional Radiology [SIR] class A and B) complications occurred in 8 cases (8.9%), while there was 1 (1.1%) major complication (SIR class F). A total of 44/90 (48.9%) patients could be reached for follow-up at 4 weeks postprocedure. In addition, 31/44 (70.5%) of these patients had a diagnosis of malignancy. Of these, 20 received chemotherapy, 8 died prior to receiving any treatment, 2 declined any further medical or surgical intervention, and 1 was treated with surgical excision and adjuvant chemotherapy. Conclusion Although recently introduced in Tanzania, TTCNB has been performed with 81.9% diagnostic accuracy and a complication rate comparable to existing literature.